Komperatif Faktor-faktor Kesiapan Untuk Berubah Pada Dinas Perhubungan Dengan Dinas Komunikasi Dan Informatika Di Kota Padang Pasca Transformasi Organisasi - Ramdani Bayu Putra; Hasmaynelis Fitri (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2019)
The current era of digitizing industry 4.0 has caused great shocks in every line of organizational activity. Therefore we need individual readiness to change. This study aims to assess the Comparative Analysis of Readiness Factors to Change in the Transportation Department with the Communication and Information Office in Padang City after Organizational Transformation. The sample of this study was 107 employees in both agencies. The research data analysis technique uses Independent samples t test and Structural equation modelings (SEM). The results of the study concluded that there were significant differences in the factors of readiness to change which included transformational leadership, learning organizations, information sharing, job satisfaction and cynicism on change. The results of the structural equation modelings (SEM) model, found the fact that transformational leadership, information sharing, job satisfaction and cynicism on change have a significant effect on readiness to change. While learning organizations have not been proven to have a significant effect on readiness to change